(3OQGSGJ NGUI aj GOGQI GdGYeGd (B/s - (3LhGO, fGLj Thbjs; (3MLGRj, gjKe Ydjs ((3YeGf(B: s (3OGQ GdGgdjI ddfTQ(B, s, 2006)
(3GdYhGed GdeDKQI aj GdaGYdjI GdJfXjejI , bjGS CKQ EOGQGc GdeYQaI aj JfXjajgG dOi GdefXeGJ GdGQOfjI , GdQbGHI GdGOGQjI hOhQgG aj JMSjf GdCOGA GdeDSSj HGJLGg JWhjQ fehPL dJMSjf GdGOGA , JMdjd caGAI haGYdjI GdbQGQGJ GdGSJQGJLjI GdeSJfOI Edi fXe GdeYdheGJ GdGOGQjI GdeMhSHI aj GdHfhcI GdJLGQjI aj GdCQOf , bjGS eOi JWHjb efXeGJ GdGYeGd dGSJQGJLjI GdJZjjQ hGdJWhjQ hCKQgG Ydi GdaGYdjI , OhQ JcfhdhLjG GdeYdheGJ aj GYGOI gfOSI YedjGJ GdCYeGd , Jbjje CKQ JWHjb GSJQGJLjGJ GdJMLje Ydi GdGOGA GdeDSSj ddTQcGJ GdUfGYjI GdGQOfjI , CKQ GdfeW GdbjGOj dQDSGA GdGbSGe Ydi GdSdhc GdGHOGYj dOi GdeQDhSjf GdeHGTQjf , bjGS GdQVG GdhXjaj dOi GdYGedjf aj GdLgGh GdeUQaj GdCQOfj hCKQg Ydi GdGOGA s
(3HjHdjhZQGajG U(B.347s
Keywords: (3GOGQI GdGYeGds